Organizational cynicism: Extending the exit, voice, loyalty, and neglect model of employees' responses to adverse conditions in the workplace - Naus, Fons; van Iterson, Ad; Roe, Robert (Human relations (New York), 2007)
We propose to extend the Exit, Voice, Loyalty, and Neglect (EVLN) model of employees' responses to adverse organizational circumstances with the construct of Organizational Cynicism. Structural equation modeling was used to fit the data provided by 159 office employees of a large Dutch trade union, who were involved in a restructuring program at the time of the research, to the postulated five-factor model. Results indicated that the model showed an acceptable fit, providing suppor t for including organizational cynicism as a distinct response in the model. Multiple regression analysis was used for the differential prediction of the five responses, using two situational variables (role conflict and autonomy), two personality variables (asser tiveness and rigidity), and selected interactions. The best predictions are obtained for exit, cynicism and loyalty. Loyalty is predicted by low role conflict and high autonomy, whereas cynicism and exit are about equally predicted by high role conflict, low autonomy, and low assertiveness.